Virtual Private Network : Architecture And Implementations - Khairul Najmi, Abdul Rani (2000)
The revolution of the networked-centric economy has transformed the way of people carrying out business activities. ln this case, the business needs new kind of communication requirements in order to be more competitive. For instance, some corporate staffs are no longer work in the same building or even in the same country with their managers. Therefore a wide area link is needed to communicate with these staffs working in the remote branches or in the fields. Another example, alliances and partnerships among enterprises have become as crucial strategies that need to be regulated by many industries to cater the pressures from business competitors. Therefore, a secure communication solution is needed to link all the joined enterprises. One of the latest emerged Wide Area Network (WAN) solutions used to fulfill all the complex communication requirements is known as Virtual Private Network (VPN), which use the Internet as the main backbone. In general, VPN has been claimed to be more flexible, effective and efficient compared to other WAN technologies. Two essential functions that make VPN as one of the best alternative WAN solutions currently : Privacy for interchange of sensitive data in a cheaper way compared to traditional WAN solutions, and Remarkable security protection of information assets transmitted over the Internet infrastructure. It is good to understand the VPN technology in details before starting to implement it. In this thesis, there will be a study on VPN in terms of its progression backgrounds, configurations, application types, solution (security) features, design framework, pros and cons with respect to other competitor technologies, Quality of Service (QoS) and Service Level Agreements (SLAs), useful lo-point plan infrastructure building, real world implementation. Hopefully this thesis can be as a useful reference or guidance for those who are really interested in designing, developing, and implementing the VPN technology. In reality, VPN is an immature and upgradable technology. There are certain loopholes in its architectures and solution features that can be enhanced. This project will focus on VPN’s technology compared to other WAN solutions in providing the best solution for the organization’s enterprise network.